2016
DOI: 10.1111/iwj.12628
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography contrast media extravasation: treatment algorithm and immediate treatment by squeezing with multiple slit incisions

Abstract: In our hospital, an adverse event reporting system was initiated that alerts the plastic surgery department immediately after suspecting contrast media extravasation injury. This system is particularly important for a large volume of extravasation during power injector use. Between March 2011 and May 2015, a retrospective chart review was performed on all patients experiencing contrast media extravasation while being treated at our hospital. Immediate treatment by squeezing with multiple slit incisions was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Study by Tsai et al of 8 cases who developed vascular compromise with 50 -80 ml of non-ionic, low osmolarity extravasate demonstrated satisfactory healing using this method [66]. A similar study by Kim et al with 23 cases (no control group) of extravasate > 50 ml also showed satisfactory response after 1 week follow-up although there was immediate temporary mild blistering [67]. A similar technique whereby multiple stab incisions were made for large volume extravasations was found to be successful in a case report by Raveendran et al [68] Similar to other techniques, limited data available to support use of this, but the simplicity is attractive and more comparative data would help assess efficacy.…”
Section: Invasive Treatmentsmentioning
confidence: 77%
“…Study by Tsai et al of 8 cases who developed vascular compromise with 50 -80 ml of non-ionic, low osmolarity extravasate demonstrated satisfactory healing using this method [66]. A similar study by Kim et al with 23 cases (no control group) of extravasate > 50 ml also showed satisfactory response after 1 week follow-up although there was immediate temporary mild blistering [67]. A similar technique whereby multiple stab incisions were made for large volume extravasations was found to be successful in a case report by Raveendran et al [68] Similar to other techniques, limited data available to support use of this, but the simplicity is attractive and more comparative data would help assess efficacy.…”
Section: Invasive Treatmentsmentioning
confidence: 77%
“…Thirty-five papers were deemed eligible for inclusion after studies in which conservative management or no intervention were excluded. The requisite data were immediately available in 26 study reports 4,10,[19][20][21][22][23][24][25][26][27][28]11,[29][30][31][32][33][34][12][13][14][15][16][17][18] and the authors of the remaining nine studies 5,[35][36][37][38][39][40][41][42] were contacted twice with additional requests, mainly for exclusively paediatric extravasation data, and given at least two months to reply. Unfortunately, none of the authors were able to provide these data and those studies were excluded.…”
Section: Search Strategymentioning
confidence: 99%
“…In 2016 Kim et al [5] published an account of 23 patients with contrast medium extravasation who reported severe pressure on the limb or cases in which the extravasation volume was greater than 50 ml. The squeezing technique was applied to all 23 patients, with extravasation volumes ranging from 5 to 140 ml.…”
Section: Manual Squeezing Techniquementioning
confidence: 99%